Pengembangan Survei Kebutuhan Pendidikan Dan Pelatihan Kepariwisataan: Peningkatkan Kapasitas Masyarakat Desa Sanrobone, Kabupaten Takalar: Tourism Education and Training Needs Survey: Capacity Building for Sanrobone Village Community, Takalar Regency - Ratna; Ery, Anda Prasetyo (Politeknik Pariwisata Makassar, 2024)
Takalar Regency, South Sulawesi, possesses diverse tourism potential encompassing nature, culture, history, marine, and man-made attractions. Tourism development in this region contributes to the improvement of the local economy. However, based on observations and needs analysis conducted by the Community Service team from Makassar Tourism Polytechnic, training is necessary. Tourism managers of Sanrobone Village require collaboration between the government, educational institutions, and local communities. The tourism training program implemented by Makassar Tourism Polytechnic aims to support the development and improvement of human resource quality in Sanrobone Village, Takalar Regency, as well as increase tourism knowledge and awareness among local communities. Through this program, it is expected to assist in the development and management of Sanrobone Village to become an excellent tourist village. The interactive method of delivering material that considers participants' needs is key to the success of this program. The materials include Tourism Awareness and Sapta Pesona, Service Excellence, Digital Marketing, and an explanation of the requirements to meet the ADWI criteria. The conclusion from the training implementation is to maximize the natural, cultural, and historical potential in Sanrobone Village, thus impacting the increase of community tourism awareness in the environment surrounding the Tourist Attraction. Human resource development training for managers is expected to help realize an excellent tourist village.